Promoting Cultural Site by Improving English Language Ability: An English Specific Purpose for Tourism - Dwi Astuti Wahyu Nurhayati (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2019)
This research was carried out to improve English ability of young generations of Tapakrejo village in order to promote Punden cultural sites to be tourism destination. It is specialized in practicing communicative speaking skill as the implementation of ESP for tourism. This research included into Classroom Action Research which was conducted in two cycles. The subject of this research was 20 young people of Tapakrejo village, Blitar. The data were collected using observation checklist, interview guide, and test. The result showed that there is a significant improvement of English ability from the first cycle into second cycle. The criteria that have been used to test speaking ability were fluency, pronunciation, grammar, and vocabulary. The technique used in promoting Punden Cultural site is advertising technique through four steps: (1) drawing the tourism potential, (2) creating banners, posters, and slogans that contain the information about the Punden cultural site, (3) creating directions to reach the Punden cultural site, and (4) creating articles to be uploaded in the internet. Furthermore, the tourism potential of punden cultural site was also describe in this research.